The Determinants of Banks’ Capital Adequacy Ratio: Some Evidence from South Eastern European Countries - Aktas, Rafet; AÇIKALIN, Suleyman; Bakin, Bilge; Celik, Gokhan (Journal of Economics and Behavioral Studies, 2015)
The legal authorities set the minimum capital level for the banks. Recent studies have shown that variables used to explain capital structure of non financial firms, such as size, profit, leverage, liquidity and risk, could also be helpful in understanding banksâ€™ capital structure. This paper aims to evaluate the impact of bank-dimensional and environmental factors on bankâ€™s capital adequacy ratio in South Eastern European (SEE) region. Size, profitability (ROA), leverage, liquidity, net interest margin (NIM), and risk are used as bank-dimensional explanatory variables in a feasible GLS regression model. On the other hand, economic growth rate, inflation, real interest rate, Eurozone stock market volatility index, deposit insurance coverage, and governance indicator are added to the original model to control for environmental factors. Annual data from 71 commercial banks belong to 10 different countries in SEE region for the period of 2007 â€“ 2012 is used. This region mainly consists of the â€œtransition economiesâ€ which are still experiencing the difficulties of turning into efficient market economies with high economic potentials. The results of our study show that among the bank dimensional explanatory variables size, ROA, leverage, liquidity, net interest margin and risk have statistically significant effects in determining CAR for the banks in the region. Among the environmental factors, economic growth rate, Eurozone stock market volatility index, deposit insurance coverage, and governance have statistically significant effects in determining CAR for the banks in the SEE region.